2018
DOI: 10.1016/j.jaut.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNA screening and functional studies reveal miR-483-5p as a potential driver of fibrosis in systemic sclerosis

Abstract: Our findings showed that miR-483-5p is up-regulated in the serum of SSc patients, from the early stages of the disease onwards, and indicated its potential function as a fine regulator of fibrosis in SSc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 33 publications
2
49
0
1
Order By: Relevance
“…These results indicate that miRNA-483-5p may be distinctive for conditions characterized by fibrosis of the skin [7]. Furthermore, researchers exhibited that miRNA-483-5p overexpression in endothelial cells increased the transcriptional levels of α-SMA (alpha-smooth muscle actin) and SM22A (smooth muscle protein 22-alpha)-indicators of myofibroblast differentiation [7]. Additionally, miRNA-483-5p decreased the level of Fli-1 (friend leukemia virus integration 1)-a negative regulator of extracellular matrix [7].…”
Section: Mirna-483-5pmentioning
confidence: 75%
See 3 more Smart Citations
“…These results indicate that miRNA-483-5p may be distinctive for conditions characterized by fibrosis of the skin [7]. Furthermore, researchers exhibited that miRNA-483-5p overexpression in endothelial cells increased the transcriptional levels of α-SMA (alpha-smooth muscle actin) and SM22A (smooth muscle protein 22-alpha)-indicators of myofibroblast differentiation [7]. Additionally, miRNA-483-5p decreased the level of Fli-1 (friend leukemia virus integration 1)-a negative regulator of extracellular matrix [7].…”
Section: Mirna-483-5pmentioning
confidence: 75%
“…MicroRNA-483-5p is a molecule supposed to be a specific marker for skin fibrosis. Chouri and co-workers demonstrated that miRNA-483-5p was upregulated both in localized scleroderma (22) and systemic scleroderma (107) serum samples, unlike other autoimmunologic diseases [systemic lupus erythematosus (33), Sjögren's syndrome (23)] [7]. These results indicate that miRNA-483-5p may be distinctive for conditions characterized by fibrosis of the skin [7].…”
Section: Mirna-483-5pmentioning
confidence: 98%
See 2 more Smart Citations
“…Surprisingly, despite laying a strong foundation for molecular SSc classification, these genes did not contain some of the crucial SSc‐associated genes, such as CD247 , STAT4 , TLR8 , IRF5 , IRF4 , and IRF7 . Several recent studies have shown that genetic and epigenetic profiling of specific cell types provides more information on disease mechanisms and phenotypes than whole tissue or peripheral blood mononuclear cell profiling . For example, CXCL4 has been shown to be a predictive biomarker for SSc progression and was captured by independent dendritic cell profiling or by proteomic profiling of blood and skin .…”
mentioning
confidence: 99%